Topical Application of KAJD Attenuates 2,4-Dinitrochlorobenzene-Induced Atopic Dermatitis Symptoms Through Regulation of IgE and MAPK Pathways in BALB/C Mice and Several Immune Cell Types - Hong, Se Hyang; Ku, Jin Mo; Kim, Hyo In; Kim, Tai Young; Seo, Hye Sook; Shin, Yong Cheol; Ko, Seong-Gyu (Frontiers in Pharmacology, 2019)
Atopic dermatitis (AD) is a frequent skin complication that is caused by unknown reasons. KHU-ATO-JIN-D (KAJD) is a new drug aimed at AD composed of a mixture of extracts from six plants known to have anti-inflammatory and antiallergic effects. This study investigated whether KAJD alleviates 2,4-dinitrochlorobenzene (DNCB)-induced AD in BALB/c mice and several immune cell types. We applied KAJD to DNCB-induced AD-like skin lesions in BALB/c mice, phorbol myristate acetate/ionomycin-stimulated human mast cells (HMC-1), and lipopolysaccharide (LPS)-stimulated macrophages and splenocytes. Histological, ELISA, PCR, and Western blot experiments were performed. The application of KAJD significantly attenuated the lesion severity and skin thickness and inhibited the infiltration of inflammatory cells, mast cells and CD4+ T cells into the sensitized skin of mice. Reduced leukocyte numbers and proinflammatory cytokine and IgE levels were also observed in the sera of KAJD-treated mice. Moreover, in vitro studies demonstrated that KAJD treatment reduced the LPS-induced expression of proinflammatory cytokines and nitric oxide (NO) production in RAW 264.7 cells. The regulation of IL-4 and IL-6 mRNA and MAPK pathways was also detected in agonist-induced isolated splenocytes and HMC-1 cells by the addition of KAJD. Taken together, our results demonstrate that KAJD inhibits the development of DNCB-induced AD in BALB/c mice and in several immune cell types, suggesting that KAJD might be a useful therapeutic drug for the treatment of AD.